Pengaruh Kompetensi Digital, Motivasi Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Badan Pengembangan Sumber Daya Manusia (Bpsdm) Provinsi Sulawesi Selatan - Elisnawati Elisnawati; Masdar Mas’ud; Abbas Selong (Departement of Mathematics Education, 2023)
This research was conducted at Campus II of the Human Resources Development Agency (BPSDM) of South Sulawesi Province. The purpose of this research is to find out Digital Competence, Work Motivation and Work Discipline on Employee Performance at the Human Resource Development Agency (BPSDM) of South Sulawesi Province. This type of research is quantitative with the aim of finding answers to research questions based on the actual situation that is happening. This study used a sample of 51 respondents. This sample was taken using purposive sampling. The test equipment used is the research instrument test and path analysis with the SPSS version 26.0 program. The results of this study are that digital competence variables affect employee performance variables. Work motivation variables affect employee performance variables and work discipline variables affect employee performance variables. The influence given by the digital competency, work motivation and work discipline variables has a positive and significant effect where the dominant influence on employee performance is work motivation.